Analysis of the Falcon signature compared to other signatures. GPV and Rabin frameworks - Harmash, D.V. (Radiotekhnika, 2022)
The article discusses the analysis of the essence and protection possibilities of the Falcon post-quantum signature. The main properties of the Falcon signature are considered. An estimate of what resources and computing power is required to use successfully the Falcon signature. A structural analysis of the Falcon signature is performed. The GPV and Rabina frameworks are analyzed. Detailed conclusions are made regarding the conducted analyses. The stability and complexity of the GPV and Rabin frameworks are evaluated, the main structures and protocols of these frameworks are considered. A detailed analysis of the main properties of NTRU lattices is carried out, the main rules of factorization of the GPV and Rabin frameworks are considered. Fast Fourier sampling is investigated. Conclusions are made regarding each conducted study.